A review of active inceptor systems technology - Qi, Yating; Whidborne, James F.; Lu, Linghai (Cambridge University Press (CUP), 2026)
An active inceptor is a sidestick equipped with electromechanical actuators that provide programmable haptic feedback, offering pilots a tangible sense of control and enhancing their situational awareness. By integrating real-time force feedback mechanisms, active inceptors aim to improve handling qualities, reduce pilot workload, and support safer operations, particularly under dynamic or degraded flight conditions. Unlike conventional passive sidesticks, active inceptor systems (AIS) enable adaptive cueing strategies that respond to flight dynamics, control surface behaviour, and flight control laws. This review paper examines the evolving role of AIS in fly-by-wire (FBW) architectures and emerging aircraft control systems. It outlines fundamental design philosophies, summarises recent research and case studies, analyses its integration within flight control architectures, and reviews existing certification and regulatory considerations influencing AIS deployment. In addition, the paper explores potential handling quality assessment frameworks applicable to AIS. While the primary focus of this paper is the AIS application on fixed-wing aircraft, the review also highlights its established and emerging use in rotorcraft, offers insights into potential directions for future research and integration into next-generation flight platforms.
Keywords: 4001 Aerospace Engineering; Aerospace & Aeronautics; 35 Commerce, management, tourism and services; 40 Engineering; active inceptors systems; force feedback; handling qualities; haptic feedback; pilot-in-the-loop